Natural regeneration of trees in three types of afforested stands in the Taihang Mountains, China. - Xitian Yang; Dongfeng Yan; Canran Liu (PLoS ONE)
Natural regeneration is the natural process by which plants replace themselves. It is a cost-effective way to re-establish vegetation, and it helps to preserve genetic identity and diversity. In this study, we investigated the natural regeneration of trees in three types of afforested stands in the Taihang Mountains, China, which were dominated by Robinia pseudoacacia (black locust), Quercus variabilis (Chinese cork oak) and Platycladus orientalis (Chinese arborvitae) respectively. A consistent pattern was found among the three types of stands, being that the density of seedlings was positively correlated with the overstory canopy cover and negatively correlated with the covers of shrub, herb and litter layers. While a positive correlation between the density of seedlings and stand age was found for the conifer stands, negative correlations were found for the two types of broadleaf stands. Correlations between the density of saplings and the stand attributes were not consistent among the three types of stands. The two types of broadleaf stands had higher densities of seedlings and saplings than the conifer stands. While the broadleaf stands had adequate recruits for regeneration, the conifer stands did not have enough recruits. Our findings suggest that the overstory canopy should be prevented from being disturbed, any reduction of the canopy cover will decrease the recruits and affect the regeneration.